2016
DOI: 10.1038/srep38243
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Patients–Negative Biopsy Controls Discrimination by Untargeted Metabolomics Analysis of Urine by LC-QTOF: Upstream Information on Other Omics

Abstract: The existing clinical biomarkers for prostate cancer (PCa) diagnosis are far from ideal (e.g., the prostate specific antigen (PSA) serum level suffers from lack of specificity, providing frequent false positives leading to over-diagnosis). A key step in the search for minimum invasive tests to complement or replace PSA should be supported on the changes experienced by the biochemical pathways in PCa patients as compared to negative biopsy control individuals. In this research a comprehensive global analysis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
3
33
1
Order By: Relevance
“…One other classification of biomarkers is based on the number of compounds forming part of the given biomarker. This classification is characteristic of metabolomics biomarkers, giving place to single metabolite biomarkers and panel metabolite biomarkers [10,11].…”
Section: Single and Multiple Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…One other classification of biomarkers is based on the number of compounds forming part of the given biomarker. This classification is characteristic of metabolomics biomarkers, giving place to single metabolite biomarkers and panel metabolite biomarkers [10,11].…”
Section: Single and Multiple Biomarkersmentioning
confidence: 99%
“…Since then, metabolomics has provided numerous biomarkers in the clinical area in general and in forensics in particular, despite it is hardly taken into account most times. For example, in the characterization of the salivary epigenome, the importance of previous work in dealing with the salivary microbiome, proteome, endocrine analytes, genome, and transcriptome was highlighted [37], but the possible role of metabolomics was ignored, despite its crucial importance in unraveling epigenetic behavior [10]. At present, the importance of metabolomics biomarkers increases at a fast rhythm [38,39], even surpassing wellestablished proteomics biomarkers.…”
Section: Open Accessmentioning
confidence: 99%
“…Analysis of urine has reported to improve diagnosis (sensitivity 88.4%, specificity 93%) and showed many dysregulated metabolic pathways 293 . Using MetaboAnalyst, upregulation of purine and pyramidine metabolism as well as downregulation of multiple pathways (histidine, arginine, tyrosine, tryptophan, taurine, alanine, aspartate, glutamate) was observed 293 .…”
Section: Systemic Biomarkersmentioning
confidence: 99%
“…Using MetaboAnalyst, upregulation of purine and pyramidine metabolism as well as downregulation of multiple pathways (histidine, arginine, tyrosine, tryptophan, taurine, alanine, aspartate, glutamate) was observed 293 . Other investigators have observed implicated deranged pathways including the urea and tricarboxylic acid cycle as well as amino acid and purine metabolism in urine samples 294 .…”
Section: Systemic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation